Ancient human tooth samples used for TB paleomicrobial research - Pósa, Annamária (Acta Biologica Szegediensis, 2012)
Questions about the evolution of tuberculosis and its pathogens are of primary importance in today’s research. We need a thorough understanding, both of the origins and history of the disease and of the evolutionary potential of its pathogens, in order to make valid prognoses for the future. Paleomicrobial analysis of ancient microbial DNA (aDNA) helps to identify human pathogens in human remains. During the last twenty years the application of modern biomolecular techniques, such as PCR, spoligotyping and DNA sequencing, in possible cases of skeletal tuberculosis has provided additional evidence for the differential diagnosis of ancient tuberculosis (e.g. Spigelman and Lemma 1993; Nerlich et al. 1997; Zink et al. 2001; Donoghue 2009). The presence of Mycobacterium tuberculosis (MTB) DNA in ancient human samples has confirmed morphological and radiological evidence of tuberculosis in archaeological human remains and furnished key material to understand the evolutionary history of the pathogen. The large majority of MTB aDNA studies used bone samples (mainly compact bone or vertebrae) or mummified tissues. Although, since the late nineties tooth samples have already been used successfully for the isolation of aDNA remains of other pathogens, e.g. for Yersinia pestis (Drancourt et al. 1998), they were only sporadically utilized in TB research. In a recent research project we tried to compare the preservation of mycobacterial aDNA in different bone elements and found a very heterogenous picture, indicating an important ‘chance factor’ in these researches (Pósa et al. 2012). In the newest phase of this project, tooth samples have also been used. We tested bone and tooth samples from two osteoarchaeological series from Hungary: the anthropological remains of the Bácsalmás-Óalmás and the Vésztô-Mágor sites. Our preliminary results prove the preservation of MTB aDNA in both series indicating the necessity to use parallel bone and tooth samples in further paleomicrobial analyses. Our future aims include a larger scale comparative investigation in order to precisely determine which anatomical elements of a human skeleton give the best MTB aDNA preservation.